A reexamination of real stock returns, real interest rates, real activity, and inflation: Evidence from a large data set - Paul M. Jones; Eric Olson; Mark Wohar (2017)
Using the informational sufficiency procedure from Forni and Gambetti (2014) along with data from McCracken and Ng (2014), we update the results of Lee (1992) and find that his Vector Autoregression (VAR) is informationally deficient. To correct this problem, we estimate a Factor Augmented VAR (FAVAR) and analyze the differences once informational deficiency is corrected with an emphasis on the relationship between real stock returns and inflation. In particular, we examine Modigliani and Cohn’s (1979) inflation illusion hypothesis, Fama’s (1983) proxy hypothesis, and the “anticipated policy hypothesis.”